Quality of life changes in an alcoholics anonymous self-help group - INDRĖ DIRGĖLIENĖ; DALIA KAVALIAUSKIENĖ; RASA LETUKIENĖ (Socialinis Darbas: Patirtis ir Metodai, 2017)
The issue of alcohol addiction is one of the most pressing in contemporary society as it causes an effect in the context of poverty, violence and suicidal behaviour. After the restoration of Lithuania‘s Independence a new helping profession such as social worker appeared: they were expected to provide professional help to people in order to help them find inner motivation for positive socialization or re-socialization. The issue of alcohol addiction/dependence was first viewed systemically, with the understanding of the need for systemic help: social, psychological, spiritual and medical. Long-term rehabilitation centres have been created and self-help groups formed: those of Alcoholics Anonymous (AA), Al-anon (self – help groups for friends and families who have relatives suffering from alcohol) and ACA (Adult Children of Alcoholics self-help group). The article analyzes the quality of life changes in an Alcoholics Anonymous self-help group. Qualitative survey data are presented in this article. Six life stories of people attending Alcoholics Anonymous (AA) self-help groups are provided. The age of the participants ranges from 31 to 58. The main criterion to participate in the research is: people who have or have had problems because of alcohol usage and who are Alcoholics Anonymous self-help group (AA) participants that have reached Step 12. This means they are ready to spread the message about recovering from this abuse to people who suffer from it. Deep analysis interview has been used to collect the data. Interview notional blocks are: 1) childhood experiences; 2) addiction to alcohol period and crisis; 3) changes of life quality when attending AA groups. The study data have been provided using content analysis through the deduction method. The theoretical basis is a systematic approach to a person in the course of his life‘ spiritual concepts and stages of recovery (May, 2004; Linn, Linn, 2003; Kubler-Ross, 2008) and the theory of integrated life quality (Ventegodt, Merrick, Andersen, 2003). The most important aspect of the study of ethics is cultural sensitivity and the principle of confideciality. The study was held from January to February of the year 2015. The study revealed that alcoholism is a problem which often causes concern with its consequences. And this is like a vicious circle. This addiction provides assumptions for social isolation to alcohol addicted people. In the stage of addiction the quality of life suffers. The study reveales that in the process of life change people overcome all the spiritual recovery stages: denial, anger, negotiation, depression and resignation. During the visits to AA self-help groups the life of people changes dramatically. They start seeing the meaning of life, feel life satisfaction and are happy again. The created psychological freedom and security environment context in AA self-help groups meets human needs, improves social skills and leads to better physical health. That is why it can be stated that self-help groups directly contribute to the quality of life for people with alcohol dependance problem.